CHARACTERISTICS OF THE PRODUCTION PROCESSES OF MEALS IN THE IMPLEMENTATION OF NUTRISUS IN MUNICIPALITIES OF RIO GRANDE DO NORTE - Oliva Maria da Silva Sousa; Cintia Matias Santiago; Fábio Resende de Araújo; Joana Eliza Pontes de Azevedo (Universidade do Estado do Rio de Janeiro, 2017)
This is a descriptive, cross-sectional survey which aims to evaluate the characteristics of the productive processes of meals in the implementation of NutriSus in four municipalities of Rio Grande do Norte. For the data collection, interviews and visits were carried out to the daycare centers and to the Technical Manager of each participating municipality, to make the observation and the approach of questions to evaluate how NutriSus was implemented, as well as the recordings of the interviews and transcription of the obtained audios. These data made possible the knowledge about the strategies used in each city for the implementation of the Program, in order to know if it was necessary to carry out new menu planning, implementation or adjustments in some preparations, besides verifying how is the acceptability. To achieve the expected result of the Program, it is necessary to follow the recommended administration schedule: two months of supplementation with a three or four-month interval. In the visited municipalities, it was identified that the implementation of the strategy occurred only as a pilot project, happening in some months of 2014 or 2015, not completing the cycle, without progression in 2016 and with a limited number of children. This discontinuity was due to the insufficient number of sachets sent to the municipalities by the Ministério da Saúde (Ministry of Health). It is concluded that nationalized programs that involve the three governmental spheres in their moment of implementation, such as Nutrisus, require a consistent planning, with the participation of the involved actors, which encompasses the factors necessary for its correct execution and full coverage of the target population. DOI: 10.12957/demetra.2017.25374